Analysis of Photoreceptor Rod Outer Segment Phagocytosis by RPE Cells In Situ - Sethna, Saumil (2013)
Counting rhodopsin-positive phagosomes residing in the retinal pigment epithelium (RPE) in the eye at different times of day allows a quantitative assessment of engulfment and digestion phases of diurnal RPE phagocytosis, which efficiently clears shed photoreceptor outer segment fragments (POS) from the neural retina. Comparing such activities among age- and background-matched experimental wild-type and mutant mice or rats serves to identify roles for specific proteins in the phagocytic process. Here, we describe experimental procedures for mouse eye harvest, embedding, sectioning, immunofluorescence labeling of rod POS phagosomes in RPE cells in sagittal eye sections, imaging of POS phagosomes in the RPE by laser scanning confocal microscopy, and POS quantification.